North-South and South-North : The passes in the main ridge of the East Polish Carpathians and the natural routes during the Neolithic in light of chipped stone material - Pelisiak, Andrzej (Uniwersytet Wrocławski Instytut Archeologii, 2020)
The topic addressed by this paper covers trans-Carpathian contacts during the early Neolithic, reflected both in the obsidian assemblages recovered on the Linear Pottery culture (LBK) settlement sites located in the Rzeszów-Przemyśl loess zone and the obsidian finds registered within the eastern part of the Polish Carpathians. There will be discussed routes that are alternative to the "Dukla Pass", running through mountain passes in the eastern part of the Polish Carpathians. These will be suggested based on the distribution of obsidian finds within the East Polish Carpathiansin the context of the availability of natural elements of mountain landscape that facilitated communication.This paper proposes three possible routes connecting the LBK area of inhabitationin the Rzeszów–Przemyśl loess zone and the Zone where obsidian sources were exploited in the Tokay and Zemplin Mountains: A1 – along the San, Osława and Osławka Rivers, across the Łupków Pass, along the Vyrava and Laborec Rivers; A2 – along the San and Solinka Rivers, across the Nad Roztokami Pass, and along the Cirocha, Laborec and Ondava Rivers; and A3 – along the San Riverand the Wołosaty Stream, across the Beskid Pass, and along the Uh, Latorica and Bodrog Rivers.